The Marketing Strategy for Creating a Competitive Unic Coffee & Eats in Indonesia - Suhano, Suhano; Subandi, Subandi; Endang Wahyuni, Rr.; Saidah, Deslida; Darunanto, Danang; Sumirahwati, Sumirahwati (Journal of Accounting and Finance Management, 2025)
The high demand for certain products such as organic coffee and vegan food, in business ventures such as Unic Coffee & Eat, of course, in addition to being a challenge, it will also be an obstacle if it cannot meet the demand, then this condition will be the main problem in this study. Bekasi City is currently a balancing area for DKI Jakarta as the Capital City of the Republic of Indonesia which is located to the East of Jakarta. The Baristas were much needed to process the coffee beans to become a special cafe drink, enabling them to serve classic to recent coffee drinks. The purposes of this research were to determine the internal and external factors at Unic Coffee & Eats, the strategies used to run its business for survival in the competition, and the efforts made by Unic Coffee & Eats to increase the number of consumers. The methods used are the Internal External matrix, 4K Strength Weakness Opportunity Threat Matrix, and one informant interviewed as the coffee shop owner. This research showed that the sub-total score of the internal factors of strengths was 2.44, weaknesses were 0.50, the sub-total score of the external factors of opportunities was 1.73, and threats were 0.73. The marketing strategy at Unic Coffee & Eats can be evidence that explains the internal and external factors at the coffee shop, as well as the efforts to increase its sales volume. The internal factors of Unic Coffee & Eats can serve well and have good product quality even with the price offered. On the other hand, affordable prices, quality, and service are the values for external factors that increase the number of customers in the coffee shop. It was hoped to become a reference for further research.